QingGan LiDan capsules improved alcoholic liver injury by regulating liver lipid transport and oxidative stress in mice - Fu, Zhiwen; Zhou, Jiafeng; Pan, Hongye; Yang, Song; Pan, Zhenzhen; Shen, Yujia; Yao, Jianbiao; Hu, Jiangning (Frontiers in Pharmacology, 2025)
BackgroundThe QingGan LiDan capsule (QGLD) consists of five traditional Chinese herbs, which have been used for hepatobiliary diseases such as jaundice. However, the effects and mechanisms by which QGLD prevent alcoholic liver diseases (ALD) remain unknown.Aim of the studyInvestigate the therapeutic potential of QingGan Lidan capsule (QGLD) in alleviating alcohol-induced liver injury.Materials and MethodsAcute alcoholic liver injury model and chronic and Binge ethanol Feeding Model (NIAAA) model were established. Mice were administered QGLD (360, 720, 1,440 mg/kg) or vehicle. Liver function indicators (ALT, AST), serum lipid (TC, TG), antioxidant markers (SOD, GSH, MDA), lipid metabolism/transport genes relative expression levels, liver and ileal villus morphology were analyzed. Network pharmacology analysis was also performed to identify potential targets and pathways of QGLD.ResultsQGLD reduced serum ALT, AST, hepatic TC, TG, and lipid droplet accumulation in both models. It upregulated antioxidant enzymes (SOD, GSH) and downregulated MDA. QGLD regulated the mRNA levels of genes related to the NRF2/KEAP1 pathway and lipid transport. Network pharmacology identified 221 potential targets.ConclusionQGLD mitigates alcohol-induced liver injury by reducing lipid accumulation, regulating lipid transport and enhancing antioxidant capacity. This supports its potential application in ALD management.